Shaping Charisma: Muda Waly al-Khalidi and Saint-Making in Contemporary Indonesia - Shadiqin, Sehat Ihsan (Millati: Journal of Islamic Studies and Humanities, 2024)
This article aims to clarify the social process of creating waliyullah in Muslim society. Waliyullah is often considered the highest prestige acquired by a mere human other than the Messenger. It is obtained because people perceive and believe that a person is pious and close to Allah. Most scholars explain the aspects of godliness and devotion of a figure who is regarded as a trustee or define the various teachings he conveyed and their effect on religious life. Therefore, sainthood has been a priori received. This traces the process of setting up insight on the sainthood of Abuya Muda Waly Al-Khalidi (1917-1961), a cleric who brought tarekat Naqsabandiyah Khalidiyah to Aceh in 1939 and as the top of cleric teaching genealogy of Islamic boarding school in contemporary Aceh. Data is collected by conducting several interviews with related figures, reviewing relevant documents, either the previous study result or scholar publication in various media. From this study, the author argues that sainthood is a social construction which is processed and created through political negotiations as part of strengthening religious authority.